Modern batteries : an introduction to electrochemical power sources - Vincent, Colin Angus; Scrosati, Bruno (Arnold ; Copublished in North, Central and South America by Wiley, 1997)
Based on the successful first edition, this book gives a general theoretical introduction to electrochemical power cells (excluding fuel cells) followed by a comprehensive treatment of the principle battery types - covering chemistry, fabrication characteristics and applications. There have been many changes in the field over the last decade and many new systems have been commercialised. Since the recent advent of battery powered consumer products (mobile phones, camcorders, lap-tops etc.) advanced power sources have become far more important. This text provides an up-to-date account of batteries which is accessible to anyone with a basic knowledge of chemistry and physics.